2022
DOI: 10.1021/acsami.1c22590
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermoelectric Properties of Cu2SnSe3-Based Materials with Ag2Se Addition

Abstract: In this work, (Ag, In)-co-doped Cu 2 SnSe 3 -based compounds are prepared using a self-propagating high-temperature synthesis process. Ag 2 Se and as-synthesized (Ag, In)-co-doped Cu 2 SnSe 3 -based powders are mixed in a proportion according to the formula of Cu 1.85 Ag 0.15 Sn 0.91 In 0.09 Se 3 /x Ag 2 Se (x = 0, 3, 4, and 5%), which is followed by a subsequent plasma-activated sintering (PAS) to obtain consolidated composite bulks. A sandwich experiment is designed to reveal the evolution of the microstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…62 As a result, we achieved an ultralow lattice thermal conductivity value of 0.16 W m −1 K −1 at 548 K for the H3 sample, which is significantly lower than previously reported values as shown in Figure S8. 44,56,63,64 To assess the impact of pores on the reduction of thermal conductivity, two models were employed: the effective medium theory (EMT) and Maxwell-Eucken 1 (M-E 1). 65,66 In the context of the Maxwell-Eucken (M-E 1) model, it is used to figure out the highest possible effective thermal conductivity of a composite material made of two or more different phases (i.e., continuous phase or dispersed phase).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…62 As a result, we achieved an ultralow lattice thermal conductivity value of 0.16 W m −1 K −1 at 548 K for the H3 sample, which is significantly lower than previously reported values as shown in Figure S8. 44,56,63,64 To assess the impact of pores on the reduction of thermal conductivity, two models were employed: the effective medium theory (EMT) and Maxwell-Eucken 1 (M-E 1). 65,66 In the context of the Maxwell-Eucken (M-E 1) model, it is used to figure out the highest possible effective thermal conductivity of a composite material made of two or more different phases (i.e., continuous phase or dispersed phase).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Furthermore, the presence of a secondary phase, CuSe, and a Ag-rich phase at the grain boundaries was identified as promising phonon scattering centers within the composite. As a result, the thermal conductivity of the Cu 2 SnSe 3 -based composite exhibited a remarkable reduction, up to 0.5 W m −1 K −1 achieved at 700 K. 44 Despite this progress, a further reduction in thermal conductivity is desirable for Cu 2 SnSe 3 -based materials to achieve high ZT. One effective way to reduce thermal conductivity is to introduce porosity as it increases phonon scattering at pore sites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thermoelectric phases added as nanoinclusions directly affect the PF on the basis of their carrier properties and the matrix phase; however, they reduce κ. Various thermoelectric phases such as CoSb 3 , ,,, PbTe, ,, ZnTe, SnTe, MnTe, ZnSb, Cu 2 CdSnSe 4 , PbS, Cu 2 Se, ,, Cu 2 Te, Ag 2 Te, , Ag 2 Se, FeSb 2 , MoSi 2 , MoS 2 , , full-Heusler, , Bi 2 Te 3 , CuInTe 2 , Mg 3 Sb 2 , and Bi 2 Se 3 are used as nanoinclusions. Generally, these secondary thermoelectric-based nanoinclusions are mostly added through the in situ precipitation method. ,, Secondary thermoelectric nanoinclusions with a higher efficiency than the matrix phase are preferred to retain or increase electrical properties and reduce κ .…”
Section: Classification Of Nanoinclusionsmentioning
confidence: 99%
“…(f) Electrical conductivity; (g) Seebeck coefficient; (h) thermal conductivity; and (i) ZT of the Cu 2 SnSe 3 /Ag 2 Se composite. Reprinted with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Classification Of Nanoinclusionsmentioning
confidence: 99%
“…Ecofriendly thermoelectric material Cu 2 SnSe 3 , with a zinc blende structure, has attracted extensive attention due to its constituents being abundant and free of Pb or Te. A lot of experimental studies have been performed to improve its thermoelectric performance. For instance, Hu et al reported that they improved its thermoelectric performance due to enhanced crystal symmetry via Mg doping and intensified phonon scattering from dislocations and nano-precipitates; Ming et al reported a large ZT = 1.51 in the Cu 2 Sn 0.82 In 0.18 Se 2.7 S 0.3 sample through comprehensive band structure regulation and introduction of multi-dimensional defects; and a record high ZT = 1.61 was obtained in our previous work by creating high-dense stacking faults and endo-grown nanoneedles to block mid- and low-frequency phonons in Cu 2 SnSe 3 .…”
Section: Introductionmentioning
confidence: 99%